Testing Routine Activity Theory in Mexico - Vilalta, Carlos J. (The British journal of criminology, 2021)
Using a comprehensive victimization survey data set, we develop the first test of routine activity (RA) theory in a Latin American country. Estimating a complementary log-log multilevel model of the theory in several stages, we investigate what factors in the theory predict residential burglary risk. We find that measures associated with the exposure to potential offenders, target attractiveness, target accessibility, personal guardianship, social guardianship, and natural guardianship predict residential burglary in our sample of Mexican cities. As such, residential burglary is a complex crime with multiple factors at play, for which RA theory is a suitable theory given the conciseness of its propositions and operational definitions. We foresee RA theory successfully influencing future studies of crime in the Latin American region.